2004
DOI: 10.1097/01.jcp.0000115662.45074.c3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Isradipine on Cocaine-Induced Subjective Mood

Abstract: We hypothesized that in humans, as in animals, isradipine, a dihydropyridine-class calcium channel antagonist, would antagonize cocaine's rewarding effects, based on preclinical evidence that isradipine inhibits cocaine-mediated increases in mesolimbic dopamine (DA), thereby reducing cocaine's abuse liability. Confirmation of our hypothesis would make isradipine a promising medication for treating cocaine dependence. Eighteen male and female volunteers (mean age, 32.6 years) who met Diagnostic and Statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…LCCBs also reduce the development of tolerance to morphine (Vaupel et al, 1993;Santillan et al, 1998). Interestingly, LCCBs modify vascular tone in alcohol withdrawal but not abstinence (Kähkönen (Muntaner et al, 1991;Johnson et al, 1999) and morphine (Vaupel et al, 1993, Santillan et al, 1998, while others have not (Hasegawa and Zacny 1997;Johnson et al, 2004b), and LCCBs have no effect on ethanol intoxication (Perez-Reyes et al, 1992). Some results have been considered particularly encouraging; for example, an LCCBmediated increased the ability to refuse further doses of methamphetamine (Johnson et al, 1999).…”
Section: L-type Calcium Channels: Human Studiesmentioning
confidence: 99%
“…LCCBs also reduce the development of tolerance to morphine (Vaupel et al, 1993;Santillan et al, 1998). Interestingly, LCCBs modify vascular tone in alcohol withdrawal but not abstinence (Kähkönen (Muntaner et al, 1991;Johnson et al, 1999) and morphine (Vaupel et al, 1993, Santillan et al, 1998, while others have not (Hasegawa and Zacny 1997;Johnson et al, 2004b), and LCCBs have no effect on ethanol intoxication (Perez-Reyes et al, 1992). Some results have been considered particularly encouraging; for example, an LCCBmediated increased the ability to refuse further doses of methamphetamine (Johnson et al, 1999).…”
Section: L-type Calcium Channels: Human Studiesmentioning
confidence: 99%
“…As summarized in Table III, conflicting results have been reported in preliminary clinical studies examining stimulants' abuse liability in humans [Muntaner et al, 1991;Rosse et al, 1994;Fabian and Silverstone, 1997;Johnson et al, 1999Johnson et al, , 2004Johnson et al, , 2005bMalcolm et al, 1999;Gottschalk and Kosten, 2002;Sofuoglu et al, 2003;Roache et al, 2005]. Roache et al [2005] suggested that isradipine could even increase subjective effects and reinforcement caused by cocaine use.…”
Section: Psychostimulantsmentioning
confidence: 99%
“…Isradipine attenuated blood pressure (BP) changes Sofuoglu et al [2003] SR-isradipine (15, 30 mg) No benefits on cocaine effects, abuse liability or craving Johnson et al [2004] Isradipine 30 mg 8 12 cocaine-dependent and 19 amphetamine-dependent subjects DB, Rz PC, CO; two 8-day study periods separated by at least 1 wk; EKG, heart rate (HR) and blood pressure (BP) Isradipine reduced stimulant-associated increases in BP but produced elevation of HR Johnson et al [2005a,b] SR-Isradipine 30 mg 10 12 cocaine-dependent subjects DB, PC, CO Isradipine enhanced rather than reduced subjective effects of cocaine Roache et al [2005] CBF, cerebral blood flow; CO, cross-over; DB, double-blind; OL, open-label; P, placebo; PC, placebo-controlled; Pts, patients; RCT, randomized controlled trial; Rz, randomized; mo, month; wk, week.…”
Section: Neurodegenerative Disorders Learning and Memorymentioning
confidence: 99%
“…During the experiment, measures of cognitive performance were done 30 min prior to dosing and at 30, 60, and 120 min post-dosing. Behavioural measures of euphoria, craving, and drug reinforcement also were collected at scheduled intervals ; these findings have been described elsewhere (Johnson et al, 2004 ;Roache et al, In Press).…”
Section: General Proceduresmentioning
confidence: 99%